2022
DOI: 10.1097/mpg.0000000000003653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Functional Gastrointestinal Disorders: A Cross-Sectional Study in Italian Infants and Young Children

Abstract: Objectives: Reports of prevalence of functional gastrointestinal disorders (FGIDs) in infants/toddlers are widely variable. Reasons for this variability are not yet fully understood. The objective of this study is to estimate the prevalence of FGIDs according to Rome IV criteria and to evaluate associated factors, in Italian infants and toddlers. Methods: Subjects aged 0-48 months were enrolled by general pediatricians from 3 Italian regions. Parents or legal guardians were administered questionnaires includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This phenomenon was possibly attributed to reduced sibling rivalry and competition, leading to lower stress levels, and increased individual attention from parents. 79 Though we showed that the presence of siblings had no impact on constipation prevalence, it did identify an association between compromised mental health and an increased constipation prevalence in children in Asia. Therefore, further research is needed to understand the precise mechanisms underlying the relationship between constipation and mental health in children.…”
Section: Discussionmentioning
confidence: 54%
“…This phenomenon was possibly attributed to reduced sibling rivalry and competition, leading to lower stress levels, and increased individual attention from parents. 79 Though we showed that the presence of siblings had no impact on constipation prevalence, it did identify an association between compromised mental health and an increased constipation prevalence in children in Asia. Therefore, further research is needed to understand the precise mechanisms underlying the relationship between constipation and mental health in children.…”
Section: Discussionmentioning
confidence: 54%
“…However, the conducted study showed a relationship between the age of the parents, smoking of the mother and hypodynamia of the mother during pregnancy, a positive history of the parents regarding functional diseases of the gastrointestinal tract, hypoxic-ischemic lesions of the central nervous system and body weight at birth of 2900 g and less and intestinal colic in infants. The importance of the influence of these factors was partially confirmed in the study [21].…”
Section: Discussionmentioning
confidence: 58%
“…In 2023 Cenni et al conducted a study on 740 Italian children aiming to evaluate the prevalence of FGIDs; FC resulted to be the most frequent disorder with a prevalence of 18.2% using Rome IV criteria, with a higher prevalence in children than in adolescents [ 14 ]. Another Italian study showed a similar prevalence of FC (16.1%) in children aged between 13 and 48 months [ 15 ]. Overall, FC can be defined as a common problem in children with up to 25% of visits to pediatric gastroenterologists and 3% of all general pediatric outpatient visits are due to FC [ 16 ].…”
Section: What Is the Incidence?mentioning
confidence: 86%
“…Early child nutrition is also involved in FC: breastmilk has been reported to be a protective factor [ 15 , 21 , 32 ]. De Oliveira et al confirmed a potential association between infant milk-type and childhood constipation concluding that exclusive breastfeeding in the first 6 months of age is a protective factor for constipation, with early effects on stool consistency, and later in life through epigenetic mechanisms and/or behavioral pathways [ 33 ].…”
Section: What Is the Etiology?mentioning
confidence: 99%